Muslim Minority Rights in North Western Europe: Theory and Practice - Sedgwick, Mark (Studies in interreligious dialogue, 2016)
This paper deals with the challenges presented to Northwestern European states by Muslims in terms of minority rights. It shows that many of these states have acknowledged minorities, which are granted various kinds and degrees of territorial, political, and/or cultural rights. The variety of minority rights that matters most depends on whether the minority is national, ethnic, or religious. In general, the longer-established and less controversial the minority, the more generous the rights granted. It is thus unsurprising that although for historical reasons Muslims are sometimes treated as a minority in the Balkans, they are not at present acknowledged as a minority in Northwestern Europe. Instead, they are formally granted only individual rights, and the general public discourse is about integration, not minority rights. I argue that according to most definitions, however, Muslims in Northwestern Europe are in fact a minority, as they are objectively different from the majority population in terms of religion and ethnicity, and even to some extent language, consider themselves different, and have a "relative lack of status or power". I also argue that Muslims in Northwestern Europe in fact already benefit from many standard minority cultural rights, though very unevenly. Different states grant different cultural rights, and no state grants all of them. I conclude that the current status of Muslims in Northwestern Europe may not be as bad as is sometimes thought.